Theoretical study of photoinduced ring-opening in furan - Gromov, Evgeniy; Trofimov, Alexander; Gatti, Fabien; Köppel, Horst (The journal of chemical physics, 2010)
The potential energy surfaces (PESs) of the two lowest excited singlet states of furan [correlating with the Rydberg A12(3s) and valence B12(V) states at the C2v ground-state molecular configuration] have been studied in some detail with regard to the photoinduced ring-opening reaction. The surfaces have been characterized in terms of their stationary points and points of minimum energy conical intersections along the ring-opening pathway. The optimization of the geometrical parameters has been performed with the equation of motion coupled cluster singles and doubles method. The ab initio PESs have been modeled by energy grids and Taylor series. The resulting 11-dimensional PESs reproduce the ab initio results to a good accuracy and can be used in dynamical calculations.